Identification of dysregulated microRNA expression and their potential role in the antiproliferative effect of the essential oils from four different Lippia species against the CT26.WT colon tumor cell line - Gomide, Mayna (2016)
In spite of advances in colorectal cancer treatments, approximately 1.4 million new global cases are estimated for 2015. In this sense, Brazilian plant diversity offers a multiplicity of essential oils as prospective novel anticancer compounds. This study aimed to evaluate the antiproliferative effect of the essential oils from four Lippia species in CT26.WT colon tumor cells, as a measurement of cell cycle phase distribution and microRNA expression. CT26.WT showed cell cycle arrest at G2/M phase after treatment with 100 µg/ml of Lippia alba (Mill.) N.E.Br. ex Britton & P. Wilson, Lippia sidoides Cham., and Lippia lacunosa Mart. & Schauer, Verbenaceae, essential oils and, at the same concentration, Lippia rotundifolia Cham. essential oil caused an augment of G0/G1 phase. The miRNA expression profiling shows change of expression in key oncogenic miRNAs genes after treatment. Our findings suggest growth inhibition mechanisms for all four essential oils on CT26.WT cells involving direct or indirect interference on cell cycle arrest and/or oncogenic miRNAs expression.